(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The study examined the effect of parenting style of urban and rural area’s working and non-working women and its influence on their adolescent’s achievement. The focus of the study is on the parenting styles of working and non-working mothers of teenage boys and girls students in urban and rural areas. For this 8 Government and 8 Private schools had been selected from urban and rural area of Raipur (CG). Among pupil 400 boys and 400 girls had been selected to find out the significant differences. Results- 1.No significant differences had been observed in the achievement of adolescent boys and girls students based on the parenting style of urban working mothers. 2.No significant differences had been observed in the achievement of adolescent boys students, mean while there had been significance differences observed in the achievement of adolescent girls students based on the parenting style of rural working mothers. 3. There had been significant differences observed in the achievement of adolescent boys students, mean while there had no significance differences been observed in the achievement of adolescent girls students based on the parenting style of urban non- working mothers. 4. No significant differences had been observed in the achievement of adolescent boys students, mean while there had been significance differences observed in the achievement of adolescent girls students based on the parenting style of rural non-working mothers.